1980
DOI: 10.1002/bbpc.19800840208
|View full text |Cite
|
Sign up to set email alerts
|

Surface Composition of Wustite

Abstract: Adsorption I Katalyse I ReaktionskinetikUsing a solid electrolyte cell inside an UHV-system the surface composition of oxides and metals can be studied at high temperatures 700 to 1OOO"C and well defined oxygen activities in the range po, = lo-'' to bar. AES-measurements on wustite have shown that at temperatures >8OO"C the composition of the surface shows the same change with the varied oxygen activity as would be expected for the bulk. At temperatures below 800 "C the change of surface oxygen content is larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Based on the former model, a variation in the oxidation state of the slag may result in the segregation of oxygen ions to the surface, which will, in turn, change the number of available reaction sites for the reaction. The decrease in the reaction rate of CO 2 with several metals [28,29,30] and with solid iron oxide [31] in some conditions has been related to such phenomena. However, Grabke and Viefhaus [31] found that, for solid iron oxide, the excess adsorption of oxygen at the surface takes place only at temperatures below 1073 K. Therefore, it may reasonably be expected that for liquid slags at much higher temperatures, the adsorption is negligible.…”
Section: A Elementary Reaction Stepsmentioning
confidence: 97%
See 2 more Smart Citations
“…Based on the former model, a variation in the oxidation state of the slag may result in the segregation of oxygen ions to the surface, which will, in turn, change the number of available reaction sites for the reaction. The decrease in the reaction rate of CO 2 with several metals [28,29,30] and with solid iron oxide [31] in some conditions has been related to such phenomena. However, Grabke and Viefhaus [31] found that, for solid iron oxide, the excess adsorption of oxygen at the surface takes place only at temperatures below 1073 K. Therefore, it may reasonably be expected that for liquid slags at much higher temperatures, the adsorption is negligible.…”
Section: A Elementary Reaction Stepsmentioning
confidence: 97%
“…The decrease in the reaction rate of CO 2 with several metals [28,29,30] and with solid iron oxide [31] in some conditions has been related to such phenomena. However, Grabke and Viefhaus [31] found that, for solid iron oxide, the excess adsorption of oxygen at the surface takes place only at temperatures below 1073 K. Therefore, it may reasonably be expected that for liquid slags at much higher temperatures, the adsorption is negligible. The anticipation is in accord with the findings of Kidd and Gaskell [32] and Bhattacharyya and Gaskell, [33] who examined the dependence of surface tension of liquid FeO x on oxygen potential.…”
Section: A Elementary Reaction Stepsmentioning
confidence: 97%
See 1 more Smart Citation
“…[58] However, Grabke and Viefhaus [58] found that for wustite, adsorption occurs, only at temperatures lower than 1073 K. The surface structure of oxide melts at high temperature and dependence on oxygen potential has not yet been fully understood. Measurements by Gaskell and his group [59,60] on liquid iron oxide at 1673 K showed that the surface tension of liquid iron oxide is approximately constant with Fe 3ϩ /Fe 2ϩ .…”
Section: Change In the Surface Structure Of The Slagmentioning
confidence: 98%
“…Grabke and Viefhaus [58] have discussed that dissociation of CO 2 on the surface of solid wustite may involve formation of singly or doubly charged CO 2 ions. Assuming that the introduction of oxygen ions into the iron oxide melt may involve formation of single charge CO 2 ions instead of double charge ions , dissociation of CO 2(ad) can be further broken into two elementary reactions:…”
Section: Transfer Of Single Charge In the Rate-controlling Step Reactionmentioning
confidence: 99%